INTERACTION BETWEEN THE SETTING ASIDE OF AN AWARD AND LEAVE FOR ENFORCEMENT - Sujayadi Sujayadi (Yuridika, 2015)
Karaha Bodas case is a notorious case which demonstrates how is unpredictable of the Indonesian court’s practice when facing cases related to arbitration. This case shows various aberrations of the principles that have been commonly accepted in international commercial arbitration but distorted in practice, especially in Indonesia, therefore many experts in the field of international commercial arbitration always mention this case as a “pathology” in international commercial arbitration.[1] This article will examine the interaction between the attempt to set aside of the award, while on the other hand the successful party requests for enforcement in other jurisdictions. The discussion will be focused on the standings of the U.S. courts toward the annulment proceeding in and the judgement of the District Court of Central Jakarta. The findings in this article show that the U.S. courts – like any other jurisdictions – disobeyed the judgement of the annulment which was rendered by Indonesian court, because Indonesian courts were the secondary jurisdiction. In addition, the courts in which the enforcement sought may have discretion whether they will or will not enforce an award which has been vacated in the country of origin. The discretion is guaranteed under the New York Convention 1958.